What is so (Un)Exceptional About Soviet Cinema? The Pragmatics of Soviet Film Exports to Germany and France in the 1920s - Puchenkina, Nataliya (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article discusses Soviet the efforts to export its cinematic production to Germany and France during the 1920s. Aside from advertising the USSR’s achievements abroad, cinema export was an important contribution to early Soviet fund-raising strategies. By examining the opening of the Soviet film industry to international practices and contacts, this article seeks to challenge some assumptions of Soviet particularism in the field of its film export practices. The article begins by exploring the international roots of what was about to become the Soviet film industry and demonstrates how Soviet trade practitioners sought to benefit from them. Then, the article argues that despite several country-specific organisational and material constraints, Soviet strategies and methods of film export to Germany and France paralleled in many ways those of their Western counterparts.